Bioenergy and Value-Added Chemicals Derived Through Electrocatalytic Upgradation of Biomass: a Critical Review - Shah M.A.; Farooq W.; Shahnaz T.; Akilarasan M. (Springer, 2025)
Electrocatalytic upgradation of biomass for chemicals and energy production is an emerging approach to address the environmental issues related to chemicals and energy production. If coupled with renewable energy, this approach will further enhance the sustainability goals for the future energy and chemical sector. This work critically reviews the progress on oxidative and reductive electrocatalytic upgrading of biomass-derived chemicals such as glycerol, sorbitol, levulinic acid, 5-hydroxymethylfurfural, furfural, and bio-oil to value-added products, including 2.5-dimethyl tetrahydrofuran, 2.5-dihydroxy methyl tetrahydro furan, 2-hydroxymethyl-5-(methyl amino methyl) furan, and 2,5-furan dicarboxylic acid with simulations production of hydrogen (H2) energy. The role of the mediator in electrocatalytic upgradation serves as a high-efficiency catalytic platform for oxidation and reduction reactions. Pd and Ru exhibit promising attributes such as durability and superior electrocatalytic hydrogenation performance. Additionally, this review discusses various methods for enhancing biofuel through a multitude of approaches, such as hydrocracking, hydrotreatment, supercritical fluid processing, steam reforming, catalytic cracking, esterification, emulsification, hydrodeoxygenation, and electrocatalytic hydrogenation. Techno-economic assessment of electrocatalytic conversion of biomass to chemicals and energy are explored to identify the key contributing factors toward the economic viability of electrocatalytic upgradation of biomass for chemical and energy. Finally, research gaps are identified for further work along with economic assessment of electrocatalytic upgradation of biomass technology with and without integration of renewable energy. Graphical Abstract: (Figure presented.) ? The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.